The Urban pattern : city planning and design - Gallion, Arthur B.; Eisner, Simon (New York : Van Nostrand Reinhold Company, Inc., 1963)
The book and the concepts contained herein will encourage readers to fulfill their professional potential and expand their abilities to better serve the public they represent consistent with the highest ethical standards. The reorganization and additions to the book are a response to the changes that have taken place in recent years in the urban design profession and should be of interest to both novice and professional.
Part 1. The city of the past -- Part 2. The industrial city -- Part 3. The planning process -- Part 4. The city today -- Part 5. New Horizons -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: CITY PLANNING